Evaluating the Impact of Capacity Building on Sustainability Adherence Among Tourism Enterprises in Kenya - Ruth Kimaiga; Anthony Pepela (CV. Vocezmi Learnov, 2026)
This study investigates how capacity building enables tourism enterprises in Kenya to translate external sustainability pressures into firm-level sustainability practices. The research specifically examines the relationship between capacity-building interventions and sustainability adherence within the tourism sector in a developing-country context. The study employed a descriptive survey research design targeting 17,654 registered tourism enterprises in Kenya. A sample of 396 enterprises was selected using probability-proportional-to-size sampling. Data were analyzed using descriptive statistics and regression analysis. The research instrument demonstrated high reliability (Cronbach’s α = 0.908). Grounded in Institutional Theory and Dynamic Capabilities Theory, the study extends theoretical understanding by demonstrating that external institutional pressures alone are insufficient to ensure sustainability adherence without internal organizational capacity. The study also operationalizes Dynamic Capabilities Theory within the context of sustainable tourism in emerging economies. The findings identify capacity building as a critical driver of sustainability compliance. The study recommends shifting from enforcement-oriented approaches toward incentivized training, knowledge development, and organizational capability enhancement to improve sustainability performance in tourism enterprises. The study focuses solely on tourism enterprises in Kenya, limiting broader generalization. However, the findings provide important empirical evidence for future sustainability research and policy development in emerging economies.